The copyright quotation exception: not fair use by another name. (2nd January 2019) - Parkin, Jane
ABSTRACT: This article considers the quotation exception to copyright infringement under EU and UK law. It challenges the broad interpretation of the exception offered by academic commentators to date, as approximating a US-style fair use defence to copyright infringement, and presents an alternative understanding of the exception in its place. According to that understanding, established principles of EU and UK copyright law, including those adopted by the Court of Justice of the European Union in Deckmyn with respect to the parody exception, limit the acts permitted under the quotation exception to (1) reproductions of copyright material that are (2) identified as reproductions and (3) for a purpose of criticism, review, or an analogous purpose.